Analisis Konseptual Pengembangan Kurikulum: Tinjauan Model, Prosedur, dan Realita Implementasi di Era Modern - Ika Dian Nur Rizki; Sunhaji; Musa (Advances In Education Journal, 2026)
This article conducts a critical conceptual analysis of curriculum development by reviewing its models, procedures, and the reality of implementation in the modern era. Using the library research method based on Mestika Zed's theory, this study compares theoretical designs on paper with sociological dynamics in the field. The results show that 21st-century curriculum development requires a shift from rigid administrative documents into a living ecosystem that adapts to digital disruption. Through the exploration of various models including an in-depth analysis of Carl Rogers' humanistic model this article highlights the importance of student-centered learning to fulfill affective needs. However, there is still a wide gap between central regulations and classroom realities, driven by unequal infrastructure and the administrative burden on teachers. Systemic synergy is required to reduce these practical obstacles to create a realistic, quality, and globally competitive curriculum.